Concomitant Effects of Metformin and Vitamin C on Indomethacin-Induced Gastric Ulcer in Rats: Biochemical and Histopathological Approach - Khezri, Mohammad Rafi; Varzandeh, Reza; Ghasemnejad-Berenji, Morteza (Drug Research, 2024)
Introduction Gastric ulcer is one of the most common and serious conditions in the gastrointestinal tract. One of the main causes of gastric ulcers is using of non-steroidal anti-inflammatory drugs (NSAIDs) which have limited their use in clinical practice. Several studies have revealed that metformin and Vitamin C (Vit C) exhibit protective effects against gastric mucosal damage in different animal models. However, no studies indicate their combination's effect on gastric ulcer models. Therefore, this study aims to investigate the protective effects of metformin and Vit C combination on indomethacin-induced gastric ulcers.Material and methods In total, thirty rats were divided into six groups, including the control group, rats received indomethacin (50 mg/kg, i.p.), rats received indomethacin and pretreated with ranitidine (100 mg/kg), metformin (100 mg/kg, i.p.), Vit C (100 mg/kg), or metformin combined with Vit C. Four hours after indomethacin administration, rats were euthanized, and gastric tissues were removed for macroscopic, histopathologic, and biochemical examinations.Results All therapeutics used in this study were found to alleviate gastric mucosal injury caused by indomethacin, as observed in histopathologic and macroscopic evaluations. Both Vit C and metformin were observed to significantly decrease lipid peroxidation and enhance the activity of anti-oxidative enzymes, SOD, GPx, and catalase. However, a more significant effectiveness was observed in catalase and GPx activities when Vit C was co-administered with metformin.Conclusions In conclusion, the present study revealed that metformin and Vit C combination therapy could potentially treat gastric ulcers associated with indomethacin.
Keywords: indomethacin; metformin; gastric ulcer; vitamin C; oxidative stress